Raster Scanning of Bathymetric Plotting Sheets - Louvart, L. (The International Hydrographic Review, 2015)
Raster scanning of the Service hydrographique et océanographique de la Marine (SHOM)’s bathymetric plotting sheets provides neural networks’ with an excellent opportunity to confirm their strong capability compared with traditional computer methods in recognizing hand-written characters. This article describes the various stages necessary and comments on the first results obtained with recently acquired software referred to as RETINE.